STUDY OF THE INCIDENCE OF OSTEOMIOARTICUARY INJURIES IN BODYBUILDERS IN THE CITY OF ANÁPOLIS, GOIÁS (CIPEEX, 2022)
SINCE THE LAST DECADES, WITH THE POPULARIZATION OF THE BEAUTY STANDARD, PHYSICAL TRAINING HAS RECEIVED GREAT ATTENTION FROM THE PUBLIC. BOTH BECAUSE OF THE MEDIA APPEALS, RELATED TO BEAUTY AND AESTHETIC STANDARDS, AS WELL AS THE ASPIRATION FOR IMPROVEMENTS IN HEALTH AND WELL-BEING, OR EVEN THE DESIRE FOR THE COMPETITIVE ASPECT OF THE SPORT, THUS ATTRACTING MANY BODYBUILDERS.THEREFORE, THE LITERATURE, BASED ON PHYSIOLOGY, PSYCHOPHYSICS, BIOMECHANICS AND EPIDEMIOLOGY, POINTS OUT THE RISKS OF PRACTICING THIS SPORT, BUT ALSO POINTS OUT THE IMPORTANCE OF SOME EXERCISES THAT INVOLVE WEIGHT LIFTING DURING TRAINING.IN BODYBUILDING, AMONG THE RISK FACTORS REPORTED THAT PREDISPOSE TO A HIGHER INCIDENCE OF OSTEOMYOARTICULAR INJURY, ARE EXERCISES PERFORMED INCORRECTLY OR DUE TO LACK OF TECHNIQUE, EXCESSIVE WEIGHTS, NON-PRACTICE OF WARM-UP AND STRETCHING BEFORE TRAINING AND LACK OF FOLLOW-UP. ABOVE. TEACHERS IN TRAINING (SOUZA; MOREIRA; CAMPOS, 2015; OLIVEIRA ET AL., 2017; RECALDE; SILVA, 2019; BERETTA ET AL., 2020). ACCORDING TO CASTRO ET AL. (2015), GYMS THAT HAD PHYSICAL THERAPY SUPPORT AND MORE ADEQUATE PROFESSIONAL ASSISTANCE, ENCOURAGING CORRECT EXERCISE TECHNIQUE, HAD LOWER INJURY RATES.THUS, IN VIEW OF THIS DECLARED DUALITY BETWEEN IMPROVEMENT AND MALIGNANCY FACTORS, THE OBJECTIVE OF THE PRESENT STUDY IS TO INVESTIGATE THE INCIDENCE OF OSTEOMIOARTICULAR INJURIES IN BODYBUILDING, THROUGH THE ANALYSIS OF RISK FOR THE INJURY, TIME OF PRACTICE, ABSENCE OF AN AUXILIARY PROFESSIONAL, SEX, INDEX OF BODY MASS (BMI), AGE GROUP AND PREVIOUS INJURIES IN THE TWO TYPES OF TRAINING, IN ORDER TO UNDERSTAND THE BORDERLINE CONDITION THAT SEPARATES HEALTH FROM PHYSICAL DAMAGE.